Evaluation of antimicrobial photodynamic therapy with acidic methylene blue for the treatment of experimental periodontitis - de Almeida, Juliano Milanezi [UNESP]; Matheus, Henrique Rinaldi [UNESP]; Alves, Breno Edson Sendão [UNESP]; Gusman, David Jonathan Rodrigues [UNESP]; Nagata, Maria José Hitomi [UNESP]; de Abreu Furquim, Elisa Mara [UNESP]; Ervolino, Edilson [UNESP] (Public Library of Science (PLoS), 2022)
Objective To investigate the security and effectiveness of antimicrobial photodynamic therapy (aPDT) with a citric acid-based methylene blue (MB) on the periodontal repair following the treatment of ligature-induced experimental periodontitis (EP) in rats. Material and methods Were used 120 male rats, randomly divided into 4 experimental groups (n = 30): no treatment (NT), SRP alone (SRP), SRP plus aPDT using conventional MB pH 7.0 (aPDT-pH7), SRP plus aPDT using acidic MB pH 1.0 (aPDT-pH1). EP was induced at day 0 by the placement of a ligature around the mandibular left first molars. Ten animals per group/period were euthanized at 14, 22 and 37 days. Histopathological, histometric (percentage of bone in the furcation [PBF]) and immunohistochemical (for tartrate-resistant acid phosphatase [TRAP] and osteocalcin [OCN]) analyses were performed. Data were statistically analyzed. Results aPDT-pH1 showed the highest PBF as compared with the other treatments. Collectively, tissues’ reaction to both dyes were controlled and healthy for the periodontium. Both aPDT protocols reduced the extent and intensity of the local inflammatory response, reduced the alveolar bone resorption, and promoted a better structural arrangement of the connective tissue as compared with SRP. TRAP expression was downregulated while OCN expression was upregulated by aPDT as compared with SRP alone. Conclusion Our data implicate that the novel MB pH 1.0 is as safe as the conventional MB for use in aPDT and raises its additional benefit of increasing the amount of alveolar bone in the furcation.